Business Management Strategies to Increase the Competitiveness of MSMEs in the Digital Era - Wasilatur Rohmah; Siti Hasmah Dita Sp; Mashudi (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the business management strategies implemented by Micro, Small, and Medium Enterprises (MSMEs) in an effort to increase competitiveness in the digital era. The digital era presents opportunities as well as challenges for MSMEs to develop and maintain their existence. The research method used is a literature study by analyzing various relevant sources such as scientific journals, books, and research reports related to business management, MSME competitiveness, and digital transformation. The results of the study indicate that adaptation to digital technology, product and service innovation, competent human resource development, and collaboration and partnership strategies are key elements in an effective business management strategy to increase MSME competitiveness in the digital era. This study provides insight for MSME actors, academics, and policy makers regarding the importance of implementing the right management strategy to face the dynamics of competition in the digital era.